Improved Singlet Oxygen Production of Zinc Phthalocyanine Bearing Pyridine-4-Thiol Groups Using Sonochemistry and Comparison with Photochemistry - Dülger Kutlu, Öznur (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2024)
The interest in research to enhance the ability of sensitizers to generate singlet oxygen using light and/or ultrasound in cancer treatment has increased significantly in recent years, and studies have attracted considerable interest. In addition, phthalocyanines (Pcs) have become increasingly important as sensitizers in photodynamic therapy (PDT) (stimulation source: light) and/or sonodynamic therapy (SDT) (stimulation source: light and ultrasound). Sonophotodynamic therapy (SPDT), a new technique that gives more effective results than PDT, is now gaining in importance. Although there are published articles on SPDT studies, studies in this field are limited. In this context, we synthesized a zinc(II) phthalocyanine molecule bearing 4-(pyridine-4-ylthio) substituents to determine its potential as a sensitizer in SPDT applications as well as PDT applications, and the structure of the synthesized complex was illuminated using FTIR,1H-NMR, UV-Vis, and MS spectroscopic techniques. When light and ultrasound were combined, the calculated ΦΔ value for zinc (II) phthalocyanine (3) increased to greater than 1, even though it was 0.76 after light excitation. When evaluating the two methods, it was observed that singlet oxygen production was greatly enhanced by the SPDT method. In this way, the research will add to the enhancement of knowledge on the subject of the SPDT method's enhancement of singlet oxygen generation.